Sztuka Wschodu czy Zachodu? Typografia XVII-wiecznych kresowych druków dzieł Łazarza Baranowicza - Socha, Klaudia (Poznańskie Studia Polonistyczne. Seria Literacka, 2025)
The article attempts to compare the characteristics of Lazar Baranovych’s texts printed in both Latin and Cyrillics scripts. The comparison is particularly interesting, given that the author is a representative of 17th-century writers from the Dnieper Ukraine who wrote in multiple languages (Latin, Polish, Church Slavonic, Russian, Ruthenian) and styles. The graphic design of their texts was adapted to their subject matter and language, yet the close relationship between the language systems lead to the emergence of a characteristic style of interpenetrating means of expression typical of the region.